Central American integration: its costs and benefits. - CACERES, Luis Rene (1994)
Identifies increased economic growth, industrialization based on intra-industry trade, and greater competition in a broader subregional market as significant benefits of economic integration for Central American countries. Costs of integration stem from the inter-country monetary flows occasioned by currency arbitrage, currency substitution, and the high transaction costs associated with inconvertibility. Calls for the establishment of coordination schemes that reach beyond the realm of macroeconomic policy.